Educational Thoughts Kh. Noer Alie on the Book Nurul Hidayah to Improve Student Thoughts at Mts Attaqwa Putra Bekasi Regency - Husein, Muhammad; Khoir, Abdul; Muntaha (Proceeding International Conference on Education, 2023)
The educational thinking of KH Noer Alie, in the book Nurul Hidayah, has an important urgency in improving student morals. This study aims to analyze KH's educational thinking. Noer Alie in Nurul Hidayah's book and identified his contribution to improving the morals of Mts students. Attaqwa Putra Bekasi. The research uses qualitative methods with a descriptive approach by conducting interviews, observation, and documentation studies, including literature and content analysis. A literature study was conducted to collect information related to KH's educational thinking. Noer Alie in the book Nurul Hidayah. Content analysis was then conducted to analyze the book's contents and identify KH's views. Noer Alie about education and development of student morals. The results of this study indicate that the educational thinking of KH. Noer Alie, in the book Nurul Hidayah significantly contributes to improving student morals. This book provides practical and comprehensive guidelines for developing good morals, including moral and ethical principles in education. KH educational thinking. Noer Alie also emphasized the importance of  a holistic approach to educating students, which involves intellectual, spiritual, social and emotional aspects